2013
DOI: 10.7589/2011-11-327
|View full text |Cite
|
Sign up to set email alerts
|

Oral Rabies Vaccination Variation in Tetracycline Biomarking Among Ohio Raccoons

Abstract: Oral rabies vaccination (ORV) programs have traditionally relied on tetracycline marking as an index to bait uptake. Whether tetracycline serves well in this capacity depends on its deposition affinity and ability to be detected consistently among tissues selected for analysis from target species. We evaluated samples from 760 hunter-harvested raccoons (Procyon lotor) from areas in Ohio where ORV had been conducted during 1998, 1999, and 2001. Tetracycline marking was evaluated within and among first premolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Even though TTCC deposition may be lower in premolar teeth than in canine teeth or mandibular bone (Algeo et al 2013;Slate et al 2014), the population TTCC response was consistent with the RVNA analysis in estimating the fractions of the raccoon population affected by ORV in this study. The top population-level models of RVNA seroconversion and TTCC response during the field trial did not include location, and thus were similar across all study cells (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Even though TTCC deposition may be lower in premolar teeth than in canine teeth or mandibular bone (Algeo et al 2013;Slate et al 2014), the population TTCC response was consistent with the RVNA analysis in estimating the fractions of the raccoon population affected by ORV in this study. The top population-level models of RVNA seroconversion and TTCC response during the field trial did not include location, and thus were similar across all study cells (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Assuming the tetracycline prevalence in our study was indicative of the response that would have been observed in an ORV naïve area, the increase in tetracycline prevalence from ,1% to 54.2% after 3 yr of baiting suggests ONRAB would have resulted in a higher antibody prevalence if ORV had not occurred previously. Even though a tetracycline biomarker can be used to assess bait consumption, it does not always signify concurrent antibody development (Rosatte et al 2008) and can vary, depending on the tissues selected for analysis (Algeo et al 2013). Partial bait consumption can result in tetracycline detection but may be insufficient for development of an antibody response (Brown et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We euthanized and tested suspect rabid animals (Lembo et al 2006, Rupprecht et al 2014) and shipped rabies positives to the CDC in Atlanta, Georgia, USA, or the New York State Department of Health (NYSDOH) Rabies Laboratory in Slingerlands, New York, USA, for confirmation and rabies virus variant typing. We sedated captured raccoons with no suggestive signs of rabies using an intramuscular injection of 5:1 ketamine:xylazine (Kreeger 1999), marked them with unique numbered ear tags, collected blood for rabies virus neutralizing antibody (rVNA) determination at CDC (Smith et al 1973, 1996) or NYSDOH (Trimarchi et al 1996), and extracted a first premolar for age and biomarker analysis (Johnston et al 1987, Algeo et al 2013). We recorded date and global positioning system (GPS) coordinates for target and non‐target captures.…”
Section: Methodsmentioning
confidence: 99%